Exploring the effects of synchronous pharyngeal electrical stimulation with swallowing carbonated water on cortical excitability in the human pharyngeal motor system. Issue 9 (8th April 2016) - Magara, J.; Michou, E.; Raginis‐Zborowska, A.; Inoue, M.; Hamdy, S.
Abstract: Background: Previous reports have revealed that excitation of human pharyngeal motor cortex can be induced by pharyngeal electrical stimulation (PES) and swallowing carbonated water (CW). This study investigated whether combining PES with swallowing (of still water, SW or CW) can potentiate this excitation in either cortical and/or brain stem areas assessed with transcranial and transcutaneous magnetic stimulation (TMS). Methods: Fourteen healthy volunteers participated and were intubated with an intraluminal catheter to record pharyngeal electromyography and deliver PES. Each participant underwent baseline corticopharyngeal, hand and craniobulbar motor‐evoked potential (MEP) measurements. Subjects were then randomized to receive each of four 10‐min interventions (PES only, ShamPES+CW, PES+CW, and PES+SW). Corticobulbar, craniobulbar and hand MEPs were then remeasured for up to 60 min and data analyzed usinganova and post hoc t ‐tests. Key Results: A two‐way rmanova for Interventions × Time‐point showed a significant corticopharyngeal interaction ( p = 0.010). One‐wayanova with post hoc t ‐tests indicated significant cortical changes with PES only at 45 ( p = 0.038) and 60 min ( p = 0.023) and ShamPES+CW immediately ( p = 0.008) but not with PES+CW or PES+SW. By contrast, there were immediate craniobulbar amplitude changes only with PES+CW ( p = 0.020) which were not sustained. Conclusions & Inferences: We conclude that only PES produced long‐term changes in corticopharyngeal excitability whereas combination stimuli were less effective. Our data suggest that PES alone rather than in combination, may be better for the patients who have difficulty in performing voluntary swallows. Abstract : This study was undertaken to investigate the effect of synchronously combining PES with swallowing CW using TMS. PES was most effective at inducing excitation in the pharyngeal motor cortex. Combination of PES and CW were less effective in producing cortical excitability but induced transient excitation in the brainstem.